Palaeohydrology: traces, tracks and trails of extreme events - Herget, Jürgen; Fontana, Alessandro (Geography of the Physical Environment, 2020)
Part A: Studies with temporal focus -- Ch.1 Global megaflood paleohydrology -- Ch.2 Flooding northern Germany: impacts and magnitudes of Middle Pleistocene glacial lake-outburst floods -- Ch.3 Outburst flood from Möhne Reservoir in May 1943 after aerial bombing -- Part B: Studies with regional focus -- Ch.4 Droughts in historical times in Europe, as derived from documentary evidence -- Ch.5 Geomorphological and geoarchaeological evidence of the Medieval deluge in the Tagliamento River (NE Italy) -- Ch.6 Inverted channels in the eastern Sahara – distribution, formation, and interpretation to enable reconstruction of paleodrainage networks -- Ch.7 Noah’s Flood – probing an ancient narrative using geoscience -- Part C: Studies with methodical and technical topics -- Ch.8 Luminescence dating in fluvial settings: overcoming the challenge of partial bleaching -- Ch.9 Large palaeomeanders in Europe: distribution, formation process, age, environments and significance -- Ch.10 Palaeostage indicators in rivers - an illustrated review -- Ch.11 High-resolution sedimentary paleoflood records in alluvial river environments - a review of recent methodological advances and application to flood hazard assessment